Performance of mechanical behavior of kenaf fibre reinforced foamed composite - Mahzabin, M.S. (American Institute of Physics Inc., 2017)
This paper investigates the mechanical properties of lightweight foamed composite (LFC) with the inclusion of kenaf fibres and superplasticizer. NaOH treated kenaf fibre contents of 0.4, 0.45 and 0.5 (by weight of cement) with 5cm length were used in composite. The density of 1000kg/m3 to 2000kg/m3 foamed concrete was used for all the tested specimens. The ratio of cement, sand and water used was 1:1.5:0.45. All the experiments were set up in accordance with International standard methods of testing. In reference to the results and discussion, the different percentages of fibre used were proven to have a lesser contribution towards compressive strength or might even have reduced the result. The results also showed that water absorption and density of the composite mortar increased as the volume of fiber increased from 0.4 to 0.5 However, a higher percentage of fiber inclusions had been recorded to have a positive contribution towards flexural and tensile splitting properties of composites. © 2017 Author(s).